2016
DOI: 10.1093/jxb/erw052
|View full text |Cite
|
Sign up to set email alerts
|

OsMPK6plays a critical role in cell differentiation during early embryogenesis inOryza sativa

Abstract: HighlightThe MAP kinase cascade controls early embryogenesis prior to axis formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 78 publications
6
39
0
Order By: Relevance
“…We therefore performed genome editing using CRISPR/Cas9 in the wild-type FAZ1 background. Unfortunately, we were not able to isolate the related loss-of-function mutants for OsMPK6 due to embryo lethality, which is consistent with the results of a previous study (Yi et al, 2016); instead, we used gene knockdown mutants produced based on RNA interference (RNAi). We found that the OsMPK6 RNAi single mutant, which showed reduced expression of OsMPK6, had reduced grain size and increased grain number per panicle compared with the wild-type FAZ1, strongly suggesting that OsMPK6 is a positive regulator of grain size and is required for panicle and spikelet development ( Figures 6A, 6B, and 6G).…”
Section: Gsn1 Acts As a Negative Regulator Of The Mapk Cascade In Coosupporting
confidence: 54%
“…We therefore performed genome editing using CRISPR/Cas9 in the wild-type FAZ1 background. Unfortunately, we were not able to isolate the related loss-of-function mutants for OsMPK6 due to embryo lethality, which is consistent with the results of a previous study (Yi et al, 2016); instead, we used gene knockdown mutants produced based on RNA interference (RNAi). We found that the OsMPK6 RNAi single mutant, which showed reduced expression of OsMPK6, had reduced grain size and increased grain number per panicle compared with the wild-type FAZ1, strongly suggesting that OsMPK6 is a positive regulator of grain size and is required for panicle and spikelet development ( Figures 6A, 6B, and 6G).…”
Section: Gsn1 Acts As a Negative Regulator Of The Mapk Cascade In Coosupporting
confidence: 54%
“…While this manuscript was in preparation, a study by Yi et al . () further confirmed this embryo lethality by analyzing heterozygous T‐DNA mutants (there referred to as OsMPK6 ). The mpk1 mutant exhibited defects in cell differentiation and arrestment of embryonic development at the globular stage (Yi et al ., ).…”
Section: Discussionmentioning
confidence: 71%
“…We demonstrated the embryo lethality of MPK1 loss of function based on abnormally small embryos and reduced germination rate (Figure 2; Tables 2 and S1). While this manuscript was in preparation, a study by Yi et al (2016) further confirmed this embryo lethality by analyzing heterozygous T-DNA mutants (there referred to as OsMPK6). The mpk1 mutant exhibited defects in cell differentiation and arrestment of embryonic development at the globular stage (Yi et al, 2016).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations